2011
DOI: 10.1111/j.1460-9592.2011.03722.x
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal penile nerve block for male pediatric circumcision – randomized comparison of ultrasound‐guided vs anatomical landmark technique

Abstract: This study does not support the routine use of ultrasound for the performance of DPNB in male pediatric circumcision. Nonetheless, an associated reduction in codeine administration postoperatively suggests some benefit in terms of postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 15 publications
4
37
3
1
Order By: Relevance
“…5 When comparing ultrasound-guided dorsal penile nerve blocks, landmark-based dorsal penile nerve blocks, and caudal epidural analgesia in 216 circumcisions, there was a difference in the percentage of patients requiring intraoperative opiates (5.5%, 63%, and 1.7%, respectively; P < 0.0001), suggesting less ultrasound-guided block patients required intraoperative opiates compared with the landmark method group (5.5% vs 63%) but similarity to the caudal epidural group (5.5% vs 1.7%). 20 O'Sullivan et al 8 found no difference in the number of patients requiring fentanyl during the intraoperative period and immediately postoperatively when comparing the ultrasound-guided dorsal penile block group with the landmark technique group (29.4% vs 37.5%; P = 0.663).…”
Section: Peripheral Nerve Blocksmentioning
confidence: 98%
“…5 When comparing ultrasound-guided dorsal penile nerve blocks, landmark-based dorsal penile nerve blocks, and caudal epidural analgesia in 216 circumcisions, there was a difference in the percentage of patients requiring intraoperative opiates (5.5%, 63%, and 1.7%, respectively; P < 0.0001), suggesting less ultrasound-guided block patients required intraoperative opiates compared with the landmark method group (5.5% vs 63%) but similarity to the caudal epidural group (5.5% vs 1.7%). 20 O'Sullivan et al 8 found no difference in the number of patients requiring fentanyl during the intraoperative period and immediately postoperatively when comparing the ultrasound-guided dorsal penile block group with the landmark technique group (29.4% vs 37.5%; P = 0.663).…”
Section: Peripheral Nerve Blocksmentioning
confidence: 98%
“…[4] Bir başka çalışma US rehberliğinde DPN bloğun kör tekniğe oranla daha etkili olduğunu ve hastaların daha az analjezik ihtiyacı olduğunu göstermiştir. [5] Bizim olgumuzda US rehberliğinde DPN Blok ile hipospadias cerrahisinde 24 saat boyunca etkin analjezi sağlanmıştır, US rehberliğinde uygulanan DPN Blok teknik olarak kolay ve emniyetli bir yöntemdir. …”
Section: Olgu Sunumuunclassified
“…Approximately 15 minutes after block placement, the patient reported complete reduction of pain. The paraphimosis was reduced without complication or discomfort.The UDPB was recently described for pediatric penile anesthesia including circumcision, dorsal slit of the foreskin, penile lacerations, and reduction of paraphimosis [1,8,9]. Herein we present the first of an UDPB in the ED with an adult.…”
mentioning
confidence: 94%
“…The UDPB reported was easy to preform and quite successful in producing a dense anesthesia of the penis. The UDPB may be a useful adjunct to oral or parenteral analgesics for painful ED procedures involving the penis, most commonly, priapism, and paraphimosis reductions [8]. The UG technique holds promise to increase success rates and decrease complications associated with traditional blind methods for penile nerve blocks.…”
mentioning
confidence: 99%